2015
DOI: 10.1038/nn.4207
|View full text |Cite
|
Sign up to set email alerts
|

Surprise! Dopamine signals mix action, value and error

Abstract: Two studies invite us to reconsider the nature of striatal dopamine signals. Accumbens dopamine appears to signal the value of overt action and prediction errors arise from deviations in these signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…Correspondingly, we performed formal model comparisons using a likelihood ratio test and found that a model including an interaction between RPE valence and surprise explained behavior better than a model including only the signed RPE (Stay/switch behavior: (2)  = 36.24, P < 0.001; Delta RTs: (2)  = 18.81, P < 0.001). This result is in line with the growing consensus that separate learning systems are at play in the human brain 28 .…”
Section: Resultssupporting
confidence: 89%
“…Correspondingly, we performed formal model comparisons using a likelihood ratio test and found that a model including an interaction between RPE valence and surprise explained behavior better than a model including only the signed RPE (Stay/switch behavior: (2)  = 36.24, P < 0.001; Delta RTs: (2)  = 18.81, P < 0.001). This result is in line with the growing consensus that separate learning systems are at play in the human brain 28 .…”
Section: Resultssupporting
confidence: 89%
“…Lesion and imaging studies suggest, for example, the costs related to effort versus delay different valuation systems (Prevost et al 2010, Rudebeck et al 2006) and produce distinct (and often uncorrelated) discounting behavior (Klein-Flügge et al 2015). Moreover, recent work has found that contrary to predictions based on a utility model of dopaminergic activity, DA linked reward signaling in the striatum is heavily influenced by whether action is necessary to get a reward (Collins & Frank 2016, Syed et al 2016). Consequently, the identification of neural signals that appear to track a pure utility signal in one type of experimental design (e.g., when rewards of different magnitudes all require some action to acquire), may fail to generalize to other paradigms.…”
Section: A Taxonomy Of Reward Processesmentioning
confidence: 77%
“…Even more recently, a study combining reinforcement learning with both go and no-go responses found that the strength of DAergic RPE signaling in the striatum was heavily moderated by whether go or nogo responses were required to harvest a reward following a reward-predicting cue (Syed et al, 2016). Expanding on these results, Hamid et al (2016) used extended analysis of striatal DA release over repeated trials to show that DA ramps encoded an expected value of action, whereas short-term phasic bursts and dips reflected prediction error updates to these expected value estimates (Collins and Frank, 2016).…”
Section: Normal and Abnormal Da Function In The Context Of Motivationmentioning
confidence: 99%